Producing Authenticity, Difference and Extremism: The Framing of Religious Converts in Dutch and Flemish Newspapers - Brandt, Nella van den (Religion & gender, 2023)
In this article, we explore the framing of religious converts by Dutch and Flemish newspapers in the period 1991–2017. We focus on the differences and commonalities in ways of talking about religious conversions to Christianity and Islam. Our approach is to probe the ‘figure’ of the convert: How is the religious convert framed and understood? We present a typology of figures of the religious convert emerging from our material, including the ‘authentic seeker’, the ‘exemplary believer’, the ‘cultural other’, the ‘victim’, the ‘opportunist’ and the ‘extremist’. This approach allows us to explore how newspapers promote particular notions of conversion, and to show that the framing of religious converts is mediated by religion, gender, race and citizenship.